Analytical approaches for proteomics and lipidomics of arsenic in algae - Freitas, Ana Cristina (2019)
Arsenic (As) is an element with a complex chemistry found in relatively high concentrations in the marine environment. A diverse group of As compounds or As species exist in the marine environment and these are of importance to human health given their potential cytotoxicity. It has been pointed out that marine algae are the origin of such As compounds, since they accumulate arsenate from seawater and metabolize it into several organoarsenic species of both lipophilic and hydrophilic nature. In this chapter, it is intended to discuss lipidomics approaches for identification of the > 70 existing lipophilic arsenic species (arsenolipids) in algae which include arsenic incorporated into phospholipids, hydrocarbons, long-chain alcohols, and polyunsaturated fatty acids. In turn, proteomic analysis will also be presented and discussed in its role, for example, to investigate whether cells show a specific response or survival strategy when under arsenic-induced stress. Research on proteome involvement in stress and tolerance to arsenic offers new tools to understand the associated physiological and biochemical mechanisms connected with different algae responses. Protein biomarkers are also of interest to enable indication of quantitative changes in some physiological parameters as the result of stress or toxicity.